A Study of the Relationship between Leadership Styles and Employee Job Satisfaction at Islamic Azad University Branches in Tehran, Iran - Hamidifar, Fatemeh (SFIMAR Research Review, 2011)
The objective of this study is to explore how at the 16 branches of Islamic Azad University, Tehran province, Iran, leadership styles (the independent variable) influence employee job satisfaction the dependent variable. Using random sampling, the researcher distributed 400 questionnaires, 386 of which were completed. This study concentrates only on non-teaching staff. The survey was administered between October and December, 2009. The researcher found that the dominant leadership styles were transformational and transactional and employees were moderately satisfied with their job. The results show that different leadership style factors will have different impacts on employee job satisfaction components. Individualized consideration and laissez-faire are strong predictors of all the job satisfaction factors.